Pengaruh Transfer Pricing, Kepemilikan Asing, Dan Intensitas Modal Terhadap Penghindaran Pajak - Nasywa Ghina; Ratna Herawati; Dian Indriana Hapsari; Purwantoro Purwantoro (Fakultas Ekonomi Universitas 45 Surabaya, 2024)
The purpose of this research is to determine the effect of transfer pricing, foreign ownership, and capital intensity on tax avoidance. Property and real estate sector companies listed on the Indonesian Stock Exchange (IDX) for the 2019-2022 period are the population of this research, selected using purposive sampling technique. The data analysis used is descriptive statistical analysis, classical assumption test, multiple linear regression analysis, and hypothesis test. This research uses SPSS 25 with 76 data samples. This research shows that transfer pricing and foreign ownership do not affect tax avoidance. On the other hand, capital intensity significantly affects tax avoidance.